INDIAN ECONOMY SINCE 1991 : ECONOMIC REFORMS AND PERFORMANCE - B A PRAKASH (SOUTH ASIA PEARSON, 2012)
This book presents the policies formulated in each sector or sub-sector, and the resultant changes, during the post-reform period (1991-2008). This volume examines the impact of economic reforms on fronts as varied as the fiscal situation of government of India, state finances, money, capital market, external sector, agriculture, industry, power, health, education, employment, unemployment and poverty.
Keywords: INDIAN ECONOMY; ECONIMIC DEVELOPMENT-INDIA; ECONOMIC HOSTORY-INDIA